Stock Market Prediction Using Deep Learning Approach (International Journal of Innovative Research in Engineering & Management, 2023)
Stock market prediction is a challenging  task that has attracted a lot of attention from both academic  and industrial communities. In recent years, deep learning  has emerged as a powerful tool for stock prediction due to its  ability to handle large amounts of complex data. In this arti cle, we review the state-of-the-art deep learning techniques  for stock prediction and provide insights into their strengths  and limitations. Specifically, we focus on the application of  recurrent neural networks (RNNs) and convolutional neural  networks (CNNs) in stock prediction, and discuss the chal lenges and opportunities for future research in this area.
Keywords: Stock Prediction; Peep Learning; CNN; RNN